The role of the tumor microenvironment in the metastasis of pancreatic cancer and immunotherapy - (:unkn) unknown (Elsevier, 2019)
Pancreatic cancer is the most aggressive type of cancer, with egregious survival rates, and is notoriously difficult to treat. Patients with pancreatic cancer are generally diagnosed at an advanced stage. Unfortunately, only a small portion of them can be treated with surgical resection. Current therapeutic approaches in pancreatic cancer involve the biochemical mechanism of the tumor microenvironment, therapeutic agents, and immunotherapy. The immunosuppressive microenvironment of pancreatic cancer is composed of T-regulatory cells, chemokines, neoplastic epithelial cells, fibroblasts, platelets, tumor-associated macrophages, pericytes, natural killer cells, and other immune cells. Pancreatic cancer is resistant to single-checkpoint immunotherapies and other therapeutic approaches such as vaccination. In this chapter, we discuss the tumor microenvironment/immunity and the immune escape mechanism of pancreatic cancer that limits the effectiveness of immunotherapeutic methods. © 2019 Elsevier Inc. All rights reserved.
Keywords: Immune suppressors; Immune surveillance; Immunotherapy; Pancreatic cancer; Tumor microenvironment